Balo’s concentric sclerosis: a case report - Özdemir, Meltem; Turan, Aynur; Dilli, Alper (The European Research Journal, 2019)
Balo’s concentric sclerosis is a rare variant of multiple sclerosis which is characterized by lesions consisting rings of demyelination alternating with areas of relatively preserved myelin. These pathological changes are reflected by characteristic magnetic resonance imaging findings. We present the imaging findings of a case of BCS who presented with an acute neurological disturbance, showed a dramatical recovery following corticosteroid therapy, and remained free of relapse for more than 1 year. Although previously considered as a fulminant and fatal disease, characteristic MRI findings of Balo’s concentric sclerosis enable earlier diagnosis and treatment, and better prognosis.